Rowing biomechanics, physiology and hydrodynamic: A systematic review - Yusof, A. A. M.; Harun, M. N.; Nasruddin, F. A.; Syahrom, A. (International Journal of Sports Medicine, 2022)
According to numerous studies, rowing performance is influenced by several factors including rower`s biomechanics, rower`s physiology, the force generated and stroke style. However, there is a missing gap linking such factors with rowing performance in the available literature. This paper aims to investigate the rowing mechanism in terms of rower anthropometry and physiology, which can impact its biomechanics and performance. The corresponding hydrodynamic force generated by the oar blade to accelerate the boat is also considered in the current study. To test the objectives, systematical online searching was conducted in search of the inclusion literature criteria. All included studies used Preferred Reporting item for Systematic Review and Meta-analysis (PRISMA) guidelines to obtain the final collection of articles for this review. In order to rate the quality of the articles, risk bias assessment was performed. A total of 35 studies were included in the assessment. The studies discussed the aspects of anthropometry and physiological of the rower, the biomechanics of the rower, corresponding hydrodynamic force on the oar blade and the rowing mechanism concerning boat performance. Based on the information obtained, an understanding of the important aspects of the rowing mechanism was achieved to provide an update for comprehensive improvement.